Consumer acceptance of fermented drinks in Malaysia - Kasron, Norzalila; Abdul Manan, Musaalbakri; Mat Azmin, Mohd Nur Hafiz; Saari, Nor Azlina; Abd Latip, Malisah (Secholian Publication, 2021)
Fermented beverages have become a powerful player in the global beverage sector because of the increased demand for health products and their nutritional benefits to societies. This study aimed to identify consumer acceptance and willingness to pay for fermented drinks developed by MARDI. It also will evaluate the market potential of products among industry players. In this study, the data was collected using structured questionnaire and face-to-face interviews focused on the population in Peninsular Malaysia. The population's selection by stratified random sampling technique and the major survey locations included mall and hypermarket. Exploratory factor analysis (EFA) was used to discover the underlying structure of observed variables. A total of 400 respondents had participated in the study. A field survey conducted showed that 54% of respondents knew about functional foods and 55% of these are aware of functional foods based on fruits were in the market. The survey found that 30% of respondents had taken fermented drinks before, while the rest had never known this drink. Age and income have a significant influence on consumers' willingness to pay fermented drinks at a reasonable price if this product is available in the Malaysian market. Government support is needed to encourage the cultivation of indigenous fruit in Malaysia. It can be done through the provision of seed subsidies and financial resources to farmers in expanding and increasing the supply of these raw materials for the production of value-added products.